Discovery of a ~1 Hz Quasi-periodic Oscillation in the Low-Mass X-Ray Binary 4U 1746–37 - Jonker, Peter G. (2000)
We have discovered a ~1 Hz quasi-periodic oscillation (QPO) present in the persistent X-ray emission of the globular cluster source, dipper, and low-mass X-ray binary (LMXB) 4U 1746-37. The QPO was also observed during type I X-ray bursts. The QPO properties resemble those of QPOs found recently in the LMXB dippers 4U 1323-62 and EXO 0748-676, which makes 4U 1746-37 the third source known to exhibit this type of QPO. We present evidence for X-ray spectral changes in this source similar to those observed in LMXBs referred to as atoll sources. We detect two states, a lower intensity and spectrally hard state and a higher intensity and spectrally soft state. This may explain the different spectral characteristics reported for 4U 1746-37 earlier. The high-intensity state resembles the banana branch state of atoll sources. The QPOs are seen only in the low-intensity state and are absent when the source is in the banana branch. This strongly suggests that either the accretion disk or an extended central source changes shape between the low-intensity state and the banana branch. Twelve bursts were detected, of which five took place while the source was on the banana branch and seven while the source was in the low-intensity state. The bursts occurring on the banana branch had an e-folding time ~3 times longer than those that occurred in the low-intensity state. Whereas previously detected dips showed a decrease in count rate of only ~15%, we found a dip in one observation for which the count rate dropped from ~200 counts s⁻¹ to ~20 counts s⁻¹. This dip lasted only ~250 s, during which clear spectral hardening occurred. This is the first time strong evidence for spectral changes during a dip have been reported for this source.